Tasavvufa Giriş (2) - Tasavvufun Tarihi (Bölüm 1) - Öztürk, Ufuk (Journal of Alevism-Bektashism Studies, 2013)
The following article is part two of the series "Jntroduction to Sufism", describes the main stages of the history of Sufism and mentions its most prominent members. The article wants to provide a basis for further studies about the history of Sufism and wishes to serve as a motivation. The subject of the Sufi orders will be discussed in a separate article. The article deals with the issue about the origin of Sufism and the impact of other religious and spiritual movements on Sufism. Jt also describes the main stages of its historical development, especially its beginnings and the time of its organization and consolidation
Keywords: keyword